2011
DOI: 10.1038/eye.2011.114
|View full text |Cite
|
Sign up to set email alerts
|

Performance in the Duke–Elder ophthalmology undergraduate prize examination and future careers in ophthalmology

Abstract: Aims Cognitive factors (eg, academic achievement) have had a significant role in selecting postgraduate surgical trainees in the past. This project sought to determine the role of a national undergraduate ophthalmology prize examination (Duke-Elder examination) in the selection of postgraduate ophthalmology trainees. This would also serve as a quality assurance exercise for the assessment, in which the ultimate aim is to encourage trainees into ophthalmology. Methods A retrospective analysis of the top 20 rank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Although the relationship may not be causal, it suggests that students attending a medical school with an ophthalmology society may have a higher chance of securing an ophthalmology training position. We were surprised to find no association between higher rates of Duke-Elder participation and higher rates of ophthalmology trainees; however, others have recently highlighted that there may be a perceived relative "unimportance" of the Duke-Elder examination during ophthalmology trainee shortlisting due to the scoring system used for shortlisting [5,6]. The points awarded for a good Duke-Elder score can be obtained elsewhere through publications, presentations, and research experience.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the relationship may not be causal, it suggests that students attending a medical school with an ophthalmology society may have a higher chance of securing an ophthalmology training position. We were surprised to find no association between higher rates of Duke-Elder participation and higher rates of ophthalmology trainees; however, others have recently highlighted that there may be a perceived relative "unimportance" of the Duke-Elder examination during ophthalmology trainee shortlisting due to the scoring system used for shortlisting [5,6]. The points awarded for a good Duke-Elder score can be obtained elsewhere through publications, presentations, and research experience.…”
Section: Discussionmentioning
confidence: 98%
“…The points awarded for a good Duke-Elder score can be obtained elsewhere through publications, presentations, and research experience. As suggested by Joshi et al [5], this insignificant weighting in the shortlist criteria may dissuade potential candidates from participating in the Duke-Elder examination.…”
Section: Discussionmentioning
confidence: 99%
“…Entrance into medical and surgical specialties is becoming increasingly competitive in the UK, particularly for neurology and neurosurgery with competition ratios of 3–1 and 10–1 respectively (McNally, ). Applications for specialist training jobs place a value on winning competitions; in the UK the Duke Elder competition for ophthalmology is a good example of how competition success provides a competitive advantage for such applications (Joshi et al, ). In Russia, surgical Olympiads are run in stages throughout the country promoting self‐study and enhancing applications into surgical specialties (Dydykin and Kapitonova, ).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies have reviewed the impact of participation in the Duke-Elder Prize on pursuing ophthalmology as a career. One study found that participants in the Duke-Elder exam were not more likely to enter ophthalmology trainee than non-participants and that the presence of an ophthalmology undergraduate society at a medical school was correlated with a 1.37-fold increase of .29.5% of students who scored in the top 20 nationally in the Duke-Elder exam subsequently entered ophthalmology training [ 15 ]. Both studies concluded that, although the Duke-Elder exam is used as part of shortlisting criteria for ophthalmology training, there may be a perceived ‘unimportance’ of the exam in comparison to other criteria and this may dissuade students from participating in the exam [ 2 , 15 ].…”
Section: Discussionmentioning
confidence: 99%